(3z(BTruth Behind Bars(3y (B: Reflections on the Fate of the Russian Revolutions - Kellogg, Paul (Canada Athabasca University Press)
Just north of the Arctic Circle is the settlement of Vorkuta, a notorious camp in the Gulag internment system that witnessed three pivotal moments in Russian history. In the 1930s, a desperate hunger strike by socialist prisoners, victims of Joseph Stalin$1 (Bs repressive regime, resulted in mass executions. In 1953, a strike by forced labourers sounded the death knell for the Stalinist forced labour system. And finally, in the late 1980s and early 1990s, a series of strikes by new, independent miners$1 (Bunions were central to overturning the Stalinist system. Paul Kellogg uses the story of Vorkuta as a frame with which to re-assess the Russian Revolution. In particular, he turns to the contributions of Iulii Martov, a contemporary of Lenin, and his analysis of the central role played in the revolution by a temporary class of peasants-in-uniform. Kellogg explores the persistence and creativity of workers$1 (Bresistance in even the darkest hours of authoritarian repression and offers new perspectives on the failure of democratic governance after the Russian Revolution.s
English
Keywords: HBTV4; Martov; Mensheviks; Bolsheviks; Russian Revolution; Vorkuta; Gulag; Arctic Gulags; Lenin; Leftists; Bolshevism; Workers Resistance; Authoritarianism; Hunger Strikes; Socialism; Miners Union; Stalinism; Trotsky; The Great Terror; The Great Purge; Substitutionism; Oral Newspaper; Solzhenitsyn